Embracing New Normal in Handling Surgical Cases - Rey B. Sulayao, Jonathan; P. Magnaye, Bella (Journal of Neonatal Surgery, 2025)
Due to COVID-19 pandemic discovered in Wuhan China in December of 2019, the Operating Room has abruptly transformed and cope up with the new normal to accommodate the needs in continuing surgical procedures. The research aimed to determine the changes that occurred in the practices in handling surgical cases before to during pandemic, identify the problems encountered in terms of safety, infection control, communication and management, and to create a practice-based guideline based on the identified problems. This study utilized concurrent triangulation mixed method design with a total population of 100 Operating Room Nurses of Private Tertiary Hospitals in Batangas. The quantitative data generated in this study through a self-report questionnaire suggest a statistically significant improvement in the practices in handling surgical cases before and during pandemic with a p value of 0.000 on the Pre-operative, Intra-Operative and Post-operative phases. The researcher was able to formulate an Operating Room Model of Metamorphosis derived from the qualitative data analysis using thematic analysis which can be utilized to further assess if there are changes in the protocols or guidelines that needs to be facilitated in the unit to match with the phase of the current situation. Therefore, a tailored fit guidelines or protocol can be coined and applied appropriately to the Operating Room. With the synthesis of both quantitative and qualitative data, the researcher arrived at a recommended guideline to further improve the practices in handling surgical cases in this pandemic time and for sustainability that can be applied in the hospitals within the community. The lessons that were learned from the COVID-19 pandemic shall lead to new strategies for a substantial rearrangement of the routine in surgical practice, ensuring quality standards and preserving safety for both health workers and the patients, thus embracing the new normal.